RegHD: Robust and Efficient Regression in Hyper-Dimensional Learning System - Hernandez-Cano, Alejandro; Zhuo, Cheng; Yin, Xunzhao; Imani, Mohsen (2021 58th ACM/IEEE Design Automation Conference (DAC), 2021)
Machine learning (ML) algorithms are key enablers to effectively assimilate and extract information from many generated data in the Internet of Things. However, running ML algorithms often results in extremely slow processing speed and high energy consumption. To achieve real-time performance with high energy efficiency and robustness, we proposed RegHD, the first regression solution based on Hyperdimensional computing. RegHD redesign a regression algorithm using strategies that more closely model the ultimate efficient learning machine: the human brain. RegHD performs regression after mapping data points into high-dimensional space using similarity preserving encoding. Due to the encoder's non-linearity, RegHD learns a regression model in an efficient and linear way. RegHD creates two set of models: Input Model to cluster data points with high similarity, and Regression Model to generate a regression model for each clustered data. During prediction, RegHD computes the output value by the weighted accumulation of all regression models, considering the model confidence obtained during similarity search. To improve RegHD efficiency, we also proposed a framework that enables RegHD model quantization while having no impact on the learning accuracy. Our evaluation shows that RegHD provides 5.6 × and 12.3 × (2.9 × and 4.2 ×) faster and energy efficient training (inference) as compared to state-of-the-art regression algorithms, while providing similar quality of learning.